PTU-067 Dual-Energy X-Ray Absorptiometry Utility in Inflammatory Bowel Disease: Bsg, Frax, Nogg or Nice?. (4th June 2013) - Ah-Moye, S; Chan, D; Kang, J-Y; Pollok, R; Neild, P; Moss, K; Poullis, A
Abstract : Introduction: Patients with inflammatory bowel disease (IBD) have a 40% higher risk of osteoporotic fractures than the general population. In 2007 the British Society of Gastroenterology (BSG) produced Guidelines for Osteoporosis in Inflammatory Bowel Disease and Coeliac Disease. In 2008 the World Health Organization created the Fracture Risk Assessment (FRAX) tool, to assess the risk of fracture in an individual aged 40 years or over. The National Osteoporosis Guideline Group (NOGG) was subsequently established to provide guidelines for the management of patient's after assessment with FRAX. In August 2012 the National Institute for Health and Clinical Excellence (NICE) published their recommendations. This study aims to compare these guidelines in IBD patients and recommendations for dual-energy X-ray absorptiometry (DXA) scan. Methods: Over a four-month period, IBD patients attending the Gastroenterology Departments' of St. George's and Queen Mary's Hospital were identified. Convenience sampling was used; all IBD patients encountered in these clinics were asked to participate. Patients were asked to complete a questionnaire, gathering information required for the BSG, NOGG and NICE osteoporosis guidelines. The BSG and NICE guidance, were used in all patients. Additional assessment with NOGG guidance were used in patients 40 years and over. The recommendation for DXA scan or not were noted. Results: 153 patients were included in the study. 73 were men and 80 were women. The mean age was 42 years with an age range of 17 to 82 years. The BSG guidelines were applicable to the entire patient group. 100 patients (65.3%) were recommended a DXA scan and 53 (34.6%) were not. The NICE guidelines were applicable to the whole patient group; with 37 (24.1%) recommended a DXA scan and 83 (54.2%) not. In patients over 40 years of age there was good concurrence between all guidelines recommending a DXA scan. The BSG guidance recommended 44 patients (63.7%), NOGG recommended 42 patients (60.8%) and NICE recommended 42 patients (60.8%). In the group less than 40 years of age, the BSG guidance recommended 56 patients (66.6%) and NICE recommended 28 (33.3%) to have a DXA scan. Conclusion: There are a number of assessment tools available to assess the risk of osteoporosis in IBD patients and identify those who should have a DXA carried out. Our study has shown that in patients 40 years and over there is a reasonable concurrence between all of these assessments. For the age group less than 40 years there appeared to be less concordance. These assessment tools need to be compared further to DXA scan results, to establish the best assessment tool for IBD patients and when to commence osteoporosis treatment. Disclosure of Interest: None Declared